The mineralogy and chemical properties of soils on granite gneiss in three climatic zones in Sri Lanka - Jusop, Shamsuddin; Salleh, Ruziah; Mohd Hanif, Ahmad Husni; Awang, Kamis (Universiti Putra Malaysia Press, 1995)
Granite gneiss occurs sporadically throughout Sri Lanka. Depending on the climatic conditions and topography of the area, the rock undergoes different degrees of chemical weathering. The mineralogy and chemical properties off four common granite gneiss soils occuning in three agro-ecological zones in Sri Lanka were studied. The soil in the wet zone is low in pH and basic exchangeable cations, while the soils in the wet zone are high in pH and basic exchangeable cations. The colour of the soils changes from yellowish-brown to red as the soils get drier, pesumably due to the presence of haematite and/or goethite. Kaolinite, halloysite and smectite are present in all the soils irrespective of the climatic conditions; the amount of halloysite decreases towards the surface. Biotite is abundant in the soil of the intermediate and dry zones, but is absent in the soil ofthe wet tone. Gibbsite is present in the highly weathered soil of the wet zone. The concentration of Ca in soil solution is dependent on the amount in the soils existing in the form of exchangeable Ca. Additionally, the solution Ca concentration is significantly correlated with the soil ECEC and the ECEC/CEC ratio.